Prospective study of functional recovery of stroke patients at three months post admission: outcomes and implications for post sstroke care provision. - Ali MF,; Aziz NA,; Aznida FAA,; Rizal AM,; Azmin S, (Penerbit UKM, 2013)
Functional recovery in the immediate post stroke period predicts the long-term prognosis of post stroke patients. Despite the advancement in stroke rehabilitation in improving the physical function of survivors, there are other factors that may influence functional recovery. We aimed to assess the functional recovery of ischaemic stroke patients attending a tertiary hospital and its associated factors in order to make recommendations for post stroke care after hospital admission. A three months prospective observational study looking at functional recovery using the Modified Barthel’s Index (MBI) and depression (Patient Heath Questionnaire-9) score of post stroke patients. There were 46 ischaemic stroke patients who were recruited for the study. At three months, only 37 patients were eligible for analysis. The mean age was 67.2 (SD 11) years with the Malays (50%) making up the majority of the patients, followed by Chinese (41.3%) and Indians (8.7%). There was a total of seven (15.2%) deaths. Hypertension was the most common risk factor (89.1%) followed by dyslipidaemia (65.2%) and diabetes mellitus (63.0%). The mean MBI difference was 45.2 (SD 27.0) with a median MBI of 17.0(IQR 33.0) at baseline compared to 85.0(IQR 42.0) at three months (p < 0.001, CI 35.98,55.45). The prevalence of depression (PHQ-9≥10) was 21.6%. Lower functional recovery was found among depressed patients (p <0.026) and among patients with recurrent stroke (p< 0.035). Significant functional recovery can be seen as early as three-months post stroke. Factors such as recurrent stroke and depression may affect functional recovery post stroke; hence should be routinely screened.